Talaqqi Method: Children's Language Development in Tahfidzul Al-Qur'an Program During Covid-19 Pandemic - Annafi Nurul Ilmi Azizah; Marhumah Marhumah; Feri Faila Sufa (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2021)
This study aims to describe the implementation of the talaqqi method in the development of language and religious values in the Qur'an tahfidzul program for early childhood applied in BA Aisyiyah Mayang Gatak. This research uses descriptive methods with a qualitative approach. The subjects of the study were the principal, Teacher Tahfidz, and Children. Data collection in this study using observation methods, interviews, and documentation. This study shows that the implementation of talaqqi method on language development in receptive language achievement is that the child will have many and varied vocabulary, can straighten the child's tongue, read letters well, children can pronounce according to the makhraj letter. The implementation of talaqqi method on the development of children's religious values can instill culture to children, invite children to love Allah SWT, Children are introduced to the Qur'an and love the Qur'an, and print a generation of praiseworthy morals. Children can understand and understand the content of the Qur'an, and children have a religious character from an early age.